Peningkatan Daya Saing Produk Seni Melalui Green Marketing Pendukung OVOP di Kabupaten Sidoarjo : Pengabdian - Rizky Nurrochmad Ismail; Mochammad Hatta; Ida Kusnawati Tjahjani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Sidoarjo Regency, known as the "City of SMEs" due to its various superior regional products supporting the One Village One Product (OVOP) program, has led to increasingly fierce competition, thus demanding product differentiation, one of which is through a Green Marketing approach. The partner in this community service is the Nabila Art Gallery SME, an aromatherapy lamp manufacturer that still faces obstacles in the form of low competitiveness due to a lack of understanding of environmentally friendly promotions, product differentiation, and the use of sustainable packaging. The objective of the activity is to increase the competitiveness of partners through the implementation of Green Marketing strategies that include Green Products, Green Advertising, and Green Brands. The implementation methods include socialization, training, implementation assistance, and achievement evaluation using surveys with 15 participants. The results show that SMEs experienced a 45% increase in understanding of the Green Marketing concept, a 38% increase in branding ability, and an average increase in sales of 22%. The application of eco-friendly labels, consumer education, and differentiation based on local uniqueness have proven relevant to boosting the position of OVOP products in Sidoarjo.